Impact of Video Self-Monitoring With Graduated Training on Implementation of Embedded Instructional Learning Trials - Bishop, Crystal D.; Snyder, Patricia A.; Crow, Robert E. (Topics in early childhood special education, 2015)
We used a multi-component single-subject experimental design across three preschool teachers to examine the effects of video self-monitoring with graduated training and feedback on the accuracy with which teachers monitored their implementation of embedded instructional learning trials. We also examined changes in teachers’ implementation of learning trials. In each self-monitoring condition, teachers observed and recorded their implemented learning trials using video and a coding form. Conditions differed in the specificity of prompts on the coding form and the type of training and feedback provided. The combination of training, coding forms with specific prompts for learning trial components, and external feedback generally resulted in more accurate self-monitoring for two of three participants and increases in the fidelity of implementation of learning trials. Findings suggest self-monitoring can be effective for increasing the fidelity with which teachers implement embedded instructional learning trials, but systematic training and feedback are important for ensuring self-monitoring accuracy.